"A capoeira é tudo o que a boca come," representações sociais no batizado e troca de cordões no grupo Gangara - Bomfim, Eduardo Evangelista Costa (2013)
Capoeira nowadays has established itself as a form of systematised knowledge of relative cohesion, which has around itself traditions and elements of Brazilian social life. This paper aims to understand how, through capoeira, bodily practices become formative elements of identity, and also understand how these practices reveal elements in the society, which are inscribed in the spirit of capoeira. Furthermore, others objectives are: map memory and ancestry in capoeira; investigate how corporeality through capoeira is established as tradition and organised knowledge, especially in the particularity of the group Gangara in Bahia, and finally analyse the baptism and exchange of strands as social situation. To access the ethnographic elements, it was used the literature, semi-structured interviews and participant observation as methodological tools. After the analysis, it was found that the body functions as the main catalyst of disputes and structuring of social values. The rituality establishes itself as marker and identifier of knowledge and ways of update social reminiscences, setting traditions through the agency of collective memory, which is mobilized through corporeality developed by capoeiristas.